Environmental impact assesments and territory: contributions from the perspective of territorial understanding, intelligence and development - Bozzano, Horacio Rodolfo (2009)
Is it possible to incorporate territorial understanding, intelligence and development (TUID) in environmental and urban impact assessments (EIAs)? In this paper we intend to provide some answers to this compelling question. We present some theoretic-methodological criteria that emerged after jointly working on approximately forty EIAs, mainly on urban environments in Argentina. There already exist treatises and unique works on EIAS, thus our team has researched to enhance them with theoretic perspectives of TUID based, among other authors, in M. Santos, E. Durkheim, M. Weber, the ENTI team and numerous contemporary Latin American authors. We will focus in those subject matters usually defined in the EIA legislation as socio-economic and socio-territorial. This way, investigating each object of study and intervention (OS/OI) we were able to find some guidelines for the analysis, common to most works and to other more particular central themes. With no intention of creating a thematic classification, we still think it useful to offer an OS/OI typology, because it helps to better direct and systematize the analysis. We established the preliminary classification shown in our research based on three criteria: activity (industrial, commercial, residential, transportation, mining, etc.), scale (small, medium, large), and intensity (degrees of occupation of the territorial environment). In the second part of the publication we introduce some macro variables: place, territorial organization, identity, mobility, accessibility and connectivity. They refer to real cases.